How MaKE First Steps can help your organisation define knowledge and build a knowledge-based customer relationship management (CRM) approach. (8th April 2009) - Sharp, Peter
Suitable definitions of knowledge for particular organisational contexts are valuable for knowledge management (KM). This paper explains why it is valuable, how they can be created effectively and discusses valuable results that have been created by doing it. The paper draws conclusions from the application of the novel approach called MaKE First Steps in three diverse organisations: a UK fast moving consumer goods (FMCG) company, a group of international postgraduate business students and a large Chinese bank. Clear patterns from this research indicate what knowledge is valuable for many organisations. Without being too prescriptive, it suggests that managers should focus their investment and time on the skills and learning of the personnel that make the organisation they work for special. In terms of CRM, this paper argues that MaKE First Steps should be applied in collaboration with organisations so that they can build success around a tailored knowledge-focused strategy.